The correlations between kinesiophobia and shoulder pain, joint position sense, quality of life, and functional performance in patients with shoulder instability: A cross-sectional study - Ahmad Talal Khiyami; Raed Saleh Almalki; Safwan Habeebullah; Nora Alkhouildi Alkhouildi; Sultan Mohammed Aldhafri; Riyadh Ghazali Banjar; Mansour Saeed Alzahrani; Ehab Mustafa Alyamany; Abdulrhman Mohammed Alharbi; Ali Saleh Alesmail; Abdullah Mohammed Alfadel; Mona Awaji Alfawd; Ahmad Mohiddin Gadah; Rawan Baleegh Alwafi (Universitas Udayana dan Diaspora Taipei Medical University, 2025)
Introduction: Shoulder pain significantly affects quality of life and functional performance. Psychological factors, particularly kinesiophobia, fear of movement due to anticipated pain or injury, are crucial to consider, as they can intensify pain and hinder recovery. This study aimed to explore the relationship between kinesiophobia and various dimensions of shoulder pain, including pain intensity, functional limitations, and quality of life. Methods: A cross-sectional study was conducted with 80 participants (60 males, 20 females) experiencing shoulder pain. Participants completed the Tampa Scale for Kinesiophobia (TSK), the Shoulder Pain and Disability Index (SPADI), and the Quality of Life Index (QOL). Spearman's correlation and regression analyses were used to assess the relationships between kinesiophobia, pain, and function. Significance was set at p ≤ 0.05. Results: A weak but statistically significant positive correlation was found between TSK and SPADI (ρ = 0.237, p = 0.027). No significant correlations were observed between TSK and QOL (ρ = −0.058, p = 0.617) or JPS at 50°, 90°, and 125° of flexion (all p > 0.05). TSK significantly predicted SPADI scores (β = 0.260, p = 0.015), with each unit increase in TSK corresponding to a 0.574-point increase in SPADI. Conclusion: Our findings indicated that higher TSK scores were associated with increased SPADI scores in individuals with shoulder instability and pain, but show little correlation with QOL or JPS.